Desarrollo de una aplicación web para el control de inventarios de la empresa “Imprenta y publicidad Cuyabeno” utilizando ASP.NET - Troya Zambrano, Leisser Fernando (2024)
A business can manage its products and orders efficiently with a web application built on ASP.NET. This technology allows you to create a modern and secure web interface, as well as develop the application logic to interact with a SQL Server database and create interactive web components. The objective of this specific project was to design an inventory control application for the company "Imprenta & Publicidad Cuyabeno" using ASP.NET. The methodology adopted involved descriptive research with a non-experimental design and data collection through surveys and direct observation, with the population and sample composed of the owner and the operator of the company. The variables of interest were the web application developed with ASP.NET and the company's inventory control. During the development of the application, computer security standards were followed according to the ISO/IEC 25010 standard, SQL Server was used for database management and Microsoft Visual Studio 2022 was used as an integrated development environment, using the .NET 6 or MVC 6 platform. As a result, an application was created that follows the Model-View-Controller design pattern, allowing the management of users with authentication and defined roles. The data is stored in SQL Server databases and integrated through the use of text boxes in the web interface.